Konflik pada Tempat Kerja Berdasarkan Gaya Kepemimpinan Toxic di Perguruan Tinggi: Systematic Literature Review - Febrisi Dwita; Leony Agustine; Supardi Supardi; Shalahuddin Shalahuddin (Universitas Islam Kadiri, 2023)
There have been many studies discussing toxic leadership styles, and their impact on organizational culture, missions, and individuals. However, it is rare to find explicit discussions about toxic leadership styles, especially in a complex and comprehensive manner in education, especially universities/universities. The term